2014
DOI: 10.1063/1.4879253
|View full text |Cite
|
Sign up to set email alerts
|

The role of donor-acceptor pairs in the excitation of Eu-ions in GaN:Eu epitaxial layers

Abstract: The nature of Eu incorporation and resulting luminescence efficiency in GaN has been extensively investigated. By performing a comparative study on GaN:Eu samples grown under a variety of controlled conditions, and using a variety of experimental techniques, the configuration of the majority site has been concluded to contain a nitrogen vacancy (V N). The nitrogen vacancy can appear in two symmetries, which has a profound impact on the luminescence and magnetic properties of the sample. The structure of the mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
38
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 37 publications
4
38
0
Order By: Relevance
“…13 Using this source, it was found that either additionally supplied oxygen or a new growth structure was necessary to attain uniform Eu incorporation and luminescence properties comparable to samples grown with the commonly used Eu source, Eu(DPM) 3 . [5][6][7][8][9][10][11][12] Also, when additional oxygen was not supplied, it was found that ∼30% of the Eu ions no longer occupied Ga sites, as is typical in GaN:Eu. 13,14 Several studies have shown that the defect environment in GaN, such as the vacancy and impurities concentrations, can be modified by controlling growth temperature.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…13 Using this source, it was found that either additionally supplied oxygen or a new growth structure was necessary to attain uniform Eu incorporation and luminescence properties comparable to samples grown with the commonly used Eu source, Eu(DPM) 3 . [5][6][7][8][9][10][11][12] Also, when additional oxygen was not supplied, it was found that ∼30% of the Eu ions no longer occupied Ga sites, as is typical in GaN:Eu. 13,14 Several studies have shown that the defect environment in GaN, such as the vacancy and impurities concentrations, can be modified by controlling growth temperature.…”
mentioning
confidence: 99%
“…This growth condition also facilitates the formation of new V Ga -O N complexes. It has been suggested that OMVPE7 contains a V Ga or V Ga -O N in its local environment, 12 and the formation of these new V Ga -O N complexes, for low temperature growth, could be the reason for the fluorescence line narrowing observed in CEES. Moreover, the formation of these complexes could also have an influence on the Eu incorporation, and the lack of precipitation on the surface, by improving the solubility limits of the Eu ions in GaN.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8] The magnetic properties of GaN:Eu and other rare earth doped GaN dilute magnetic semiconductor (DMS) systems have also been extensively investigated for spintronic applications. [9][10][11][12][13][14][15] It is known that the Eu ions will incorporate into GaN in several defect environments, and that these defect environments play an important role on the spectral position of the Eu emission, [16][17][18][19][20][21][22][23][24] and in the ability for the Eu ions to capture energy from the GaN host during the recombination of electrons and holes. [7,18,22] Extensive spectroscopic work has provided ample evidence that the two main emitting centers, referred to as Eu1 and Eu2, are complexes consisting of a Eu ion on gallium site with either a nitrogen (V N ) or (V Ga ) gallium vacancy in close proximity.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14][15] It is known that the Eu ions will incorporate into GaN in several defect environments, and that these defect environments play an important role on the spectral position of the Eu emission, [16][17][18][19][20][21][22][23][24] and in the ability for the Eu ions to capture energy from the GaN host during the recombination of electrons and holes. [7,18,22] Extensive spectroscopic work has provided ample evidence that the two main emitting centers, referred to as Eu1 and Eu2, are complexes consisting of a Eu ion on gallium site with either a nitrogen (V N ) or (V Ga ) gallium vacancy in close proximity. [20,22] Eu1 has been associated with a V N , while Eu2, which contributes the most to the emission intensity under current injection, has been associated with a V Ga .…”
Section: Introductionmentioning
confidence: 99%